Indonesian Adaptation of New Norms during The Early Phase of The Pandemic Against COVID-19 - Agustin, Helfi; Salawati, Trixie; Sulistiawan, Dedik; Solikhah, Solikhah; Wahyuningsih, Wahyuningsih; Kusumaningrum, Tanjung Anitasari; Wahyuni, Sri; Haryanti, Titik (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: The COVID-19 pandemic has spread dramatically since March 2020. At the end of May 2020, the Indonesian government stated that Indonesia would soon enter a new phase facing COVID-19. This phase forced people to adopt new living norms to suppress the spread of COVID-19. This study attempted to analyze how the society in Indonesia adapted to new norms and their relation with perceived susceptibility, severity, benefits, and barriers experienced using the Health Belief Model theory.Method: This cross-sectional study voluntarily involved 948 participants across the island of Java through an online survey conducted between June 30 to July 9 2020, with Google Forms. The indicators measured in the study were: healthy living practices, changes in healthy behaviour, perceptions of susceptibility, severity, benefits, and barriers to the COVID-19 pandemic.Results: The study found that more than half of the respondents practised a healthy lifestyle during the COVID-19 pandemic. Most of them admitted that their health behaviour was better than before the pandemic. People with positive perceptions of the benefits and barriers to COVID-19 practiced a healthy lifestyle during the pandemic better (AOR = 1.72; 95% CI = 1.20-2.48 and AOR = 2.24; 95% CI = 1.60-3.14, respectively). People who had positive perceptions of susceptibility and severity about COVID-19 problems had a higher chance of improving previous preventive behaviour (AOR = 2.06; 95% CI = 1.37-3.09 and AOR = 1.79; 95% CI = 1.20-2.69, respectively). Thus, the conclusion was Indonesian people have positive practices and perceptions about the susceptibility and severity of COVID-19, which are useful for enforcing COVID-19 preventive behaviour.